Psychodrama Guide to Addressing Self-Esteem in Vocational High School Students from an Islamic Perspective - Awalya Siska Pratiwi; Fauzan, Lutfi; Hotifah, Yuliati; Brahim, Juliana (Pamomong: Journal of Islamic Educational Counseling, 2024)
The problem of self-esteem is very closely related to and influences the emotional, social, personality, and cognitive aspects of every human being, so if this problem is not resolved immediately, it will affect other things in the future. This development research aims to create a guidebook product for counselors that is interesting and easy to understand. The guidebook is about psychodrama to overcome students’ self-esteem problems. The development used is following the development of Borg and Gall (1983). The steps used in development research up to the seventh stage are by needs, namely up to the product revision stage after material expert testing, media expert testing, and testing of potential product users (counselors) at SMK Negeri 6 Malang. The results show that the psychodrama guidebook received a score from guidance and counseling material experts with an inter-rater agreement model showing very high criteria of 1, media experts of 3.2, and potential product users (counselors) of 3.4. Based on expert assessments, it was concluded that the guidebook was very suitable for use.